Repurposing type I–F CRISPR–Cas system as a transcriptional activation tool in human cells - Chen, Yuxi (Nat Commun, 2020)
Class 2 CRISPR–Cas proteins have been widely developed as genome editing and transcriptional regulating tools. Class 1 type I CRISPR–Cas constitutes ~60% of all the CRISPR–Cas systems. However, only type I–B and I–E systems have been used to control mammalian gene expression and for genome editing. Here we demonstrate the feasibility of using type I–F system to regulate human gene expression. By fusing transcription activation domain to Pseudomonas aeruginosa type I–F Cas proteins, we activate gene transcription in human cells. In most cases, type I–F system is more efficient than other CRISPR-based systems. Transcription activation is enhanced by elongating the crRNA. In addition, we achieve multiplexed gene activation with a crRNA array. Furthermore, type I–F system activates target genes specifically without off-target transcription activation. These data demonstrate the robustness and programmability of type I–F CRISPR–Cas in human cells.